Analysis of Seventh-Grade Students' Understanding of Fraction Material Based on SOLO Taxonomy (Journal of Didactic Studies, 2023)
This study aims to describe the understanding and factors influencing students' understanding of fraction material based on the SOLO taxonomy. This qualitative descriptive research involves five purposively selected subjects based on the conformity of students' responses at each level within the SOLO taxonomy. Data collection techniques include tests and interviews. Data analysis comprises data condensation, data presentation, and conclusion. The research findings indicate that: (1) Students' understanding of fraction concepts is at the prestructural, unistructural, and extended abstract levels; students' understanding of ordering fractional numbers is at the prestructural, unistructural, multi structural, and extended abstract levels; students' understanding of solving fractional number calculations is at the prestructural, unistructural, multi structural, and relational levels; and students' understanding of solving contextual problems related to fractions is at the prestructural, unistructural, and multi structural levels. (2) Factors influencing students' understanding include students' limitations in following school lessons, low interest and learning motivation; students' confusion in understanding the taught material concepts, lack of precision in students' calculation operations; less varied exercise questions provided by teachers; and students can understand the taught material concepts but are unable to generalize their knowledge.